Incidence of respiratory tract sarcoidosis in southern and northern regions of Ukraine - Gumenyuk G.L. (Medičnì Perspektivi)
We conducted a comparative survey of incidence and prevalence of pulmonary sarcoidosis in Southern (Crimean AR) and Northern (Zhytomyr region) regions of Ukraine by means of analysis of self-referred cases and cases, revealed at prophylactic radiological examination in 2011. The incidence of sarcoidosis in Crimea was 1.08 per 100 000 adult inhabitants; the prevalence was 4,59 per 100 000. In Zhytomyr region the incidence value (2,62 per 100 000) exceeded an equivalent value in Crimea by 2,4 times. The prevalence (7,86 per 100 000) was also higher than in Crimea by 1,7 times. Taking into account a significant impact of climate factor on sarcoidosis epidemiology, the incidence and prevalence of disease in Northern and Southern regions should be considered polar as for the regions of Ukraine. This makes it possoble to conclude that mean incidence of sarcoidosis in Ukraine ranges from 1,1 to 2,6 per 100 000 adult population, whereas the prevalence – from 4,6 to 7,9 per 100 000, which is equivalent to the level of Southern European countries.